Visual Search of Experts in Medical Image Reading: The Effect of Training, Target Prevalence, and Expert Knowledge - Nakashima, Ryoichi; Kobayashi, Kazufumi; Maeda, Eriko; Yoshikawa, Takeharu; Yokosawa, Kazuhiko (Frontiers in Psychology, 2013)
The aims of this study are (a) to determine the effect of training on the multiple-target lesion search performance; and (b) to examine the effect of target prevalence on the performance of radiologists and novices. We conducted four sessions of 500 trials in a lesion search on a medical image task in which participants searched for three different target lesions. Participants were ten radiologists and novices. In each session, the prevalence of the different target lesions varied from low (2 %) to high (40 %). The sensitivity of novices was higher in the later sessions than in the first session, whereas there were no differences among sessions in radiologists. The improvement on sensitivity of novices was largely due to attenuations of false alarm errors. In addition, miss rates of the three targets did not differ in data of novices, whereas radiologists produced a higher miss rate for the highest prevalence target lesion (non-serious lesion) than for the other two lesions (serious lesions). In conclusion, (a) the training for the multiple -target lesion search task can be effective to reduce false alarm errors; and (b) the prevalence effect on lesion search can be attenuated by the multiple-target identification and the knowledge about seriousness of lesions. This suggests that acquired knowledge about normal cases and serious lesions is an important aspect of a radiologists’ skill in searching for medical lesions and their high performance levels.